Enhanced expressions of mRNA for neuropeptide Y and interleukin 1 beta in hypothalamic arcuate nuclei during adjuvant arthritis-induced anorexia in Lewis rats - Stofkova, Andrea; Haluzik, Martin; Zelezna, Blanka; Kiss, Alexander; Skurlova, Martina; Lacinova, Zdenka; Jurcovicova, Jana (Neuroimmunomodulation, 2009)
OBJECTIVE: Food intake is activated by hypothalamic orexigenic neuropeptide Y (NPY), which is mainly under the dual control of leptin and ghrelin. Rat adjuvant arthritis (AA), similarly as human rheumatoid arthritis, is associated with cachexia caused by yet unknown mechanisms. The aim of our study was to evaluate NPY expression in hypothalamic arcuate nuclei (nARC) under the conditions of AA-induced changes in leptin, ghrelin and adiponectin. Since IL-1beta is involved in the central induction of anorexia, we studied its expression in the nARC as well. METHODS: AA was induced to Lewis rats using complete Freund's adjuvant. On days 12, 15 and 18 after complete Freund's adjuvant injection, the levels of leptin, adiponectin, ghrelin and IL-1beta were determined by RIA or ELISA. The mRNA expressions for NPY, leptin receptor (OB-R), ghrelin receptor (Ghsr) and IL-1beta were determined by TaqMan RT-PCR from isolated nARC. RESULTS: In AA rats, decreased appetite, body mass and epididymal fat stores positively correlated with reduced circulating and epididymal fat leptin and adiponectin. Ghrelin plasma levels were increased. In nARC, mRNA for OB-R, Ghsr and NPY were overexpressed in AA rats. AA rats showed overexpression of mRNA for IL-1beta in nARC while circulating, and spleen IL-1beta was unaltered. CONCLUSION: During AA, overexpression of orexigenic NPY mRNA in nARC along with enhanced plasma ghrelin and lowered leptin levels occur. Decreased food intake indicates a predominant effect of the anorexigenic pathway. Activated expression of IL-1beta in nARC suggests its role in keeping AA-induced anorexia in progress. The reduction in adiponectin may also contribute to AA-induced anorexia.
Keywords: Male; Interleukin-1beta; Anorexia; adiponektin; Animals; leptin; chuť k jídlu; ghrelin; interleukin-1beta; mužské pohlaví; artritida; Arcuate Nucleus of Hypothalamus; Gene Expression Regulation; nucleus arcuatus hypothalami; Appetite Regulation; krysa rodu Rattus; potkani inbrední LEW; Adiponectin; modely nemocí na zvířatech; Rats; neuropeptid Y; nechutenství; regulace genové exprese; RNA, Messenger; regulace chuti k jídlu; Neuropeptide Y; zvířata; Appetite; upregulace; systém hypotalamus-hypofýza; Hypothalamo-Hypophyseal System; Rats, Inbred Lew; Up-Regulation; Arthritis; Signal Transduction; Leptin; Disease Models, Animal; Ghrelin; signální transdukce; messenger RNA